An appraisal ofthe rights in the African charter on human and peoples rights and notable institutions for their enforcement (2016)
This paper discusses human rights in the African Charter on Human and Peoples’ Rights (ACHPR) and notable institutions established to protect and enforce them. It aims to interrogate how the Africa Union (AU) protects human rights in the continent and the impacts of that protection. It does not address some ‘self - standing charters in the A U that have evolved and developed as separate charters on their own.1 In addition, since the focus of this paper is to examine the regional protection mechanism alone, it does not cover the issue of domestication of the ACHPR by states which is a major topic on its own. It is divided in to five sections. Section one is an introduction which discusses how the Organization of the African Unity (OAU) was formed. Section two appraises the rights in the ACHPR. The subsequent sections three and four examine the role of notable institutions established to protect and enforce human rights in the continent, while the sixth section concludes.